Roughness of Filters in Equality Algebras - Rezaei, Gholam Reza; Borzooei, Rajab Ali; Aaly Kologani, Mona; Jun, Young Bae (Bulletin of the Section of Logic, 2023)
Rough set theory is an excellent mathematical tool for the analysis of a vague description of actions in decision problems. Now, in this paper by considering the notion of an equality algebra, the notion of the lower and the upper approximations are introduced and some properties of them are given. Moreover, it is proved that the lower and the upper approximations define an interior operator and a closure operator, respectively. Also, using D-lower and D-upper approximation, conditions for a nonempty subset to be definable are provided and investigated that under which condition D-lower and D-upper approximation can be filter.